2020
DOI: 10.1590/0102-311x00190418
|View full text |Cite|
|
Sign up to set email alerts
|

Aborto inseguro no Brasil: revisão sistemática da produção científica, 2008-2018

Abstract: O objetivo deste estudo é atualizar o conhecimento sobre o aborto inseguro no país. Foi realizada uma revisão sistemática com busca e seleção de estudos via MEDLINE e LILACS, sem restrição de idiomas, no período 2008 a 2018, com avaliação da qualidade dos artigos por meio dos instrumentos elaborados pelo Instituto Joanna Briggs. Foram avaliados 50 artigos. A prevalência de aborto induzido no Brasil foi estimada por método direto em 15% no ano de 2010 e 13% no ano de 2016. Prevalências mais elevadas foram obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0
13

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(50 citation statements)
references
References 75 publications
(235 reference statements)
1
27
0
13
Order By: Relevance
“…In a review of articles on unsafe abortion in Brazil 7 , among the quantitative studies published between 2008 and 2018, most were cross-sectional, with the limitation of ensuring the temporal sequence of events. Many used small samples and, despite good methodological quality, the generalizability of their findings was limited because they referred to very specific contexts.…”
Section: Investigation Of Factors Associated With Induced Abortionmentioning
confidence: 99%
See 4 more Smart Citations
“…In a review of articles on unsafe abortion in Brazil 7 , among the quantitative studies published between 2008 and 2018, most were cross-sectional, with the limitation of ensuring the temporal sequence of events. Many used small samples and, despite good methodological quality, the generalizability of their findings was limited because they referred to very specific contexts.…”
Section: Investigation Of Factors Associated With Induced Abortionmentioning
confidence: 99%
“…Works with greater sample sizes had deficiencies in their statistical analysis and few studies reported statistical power, not including, for example, confidence intervals for their estimates of abortion prevalence. Many of the studies relied on participant accounts, obtained through interviews, to measure independent variables and induced abortion, with no validation from a different source of information 7 . Another important aspect is that many determinants were often measured using the moment of the interview as the reference, instead of the period when the abortion took place, further worsening the issue of temporality.…”
Section: Investigation Of Factors Associated With Induced Abortionmentioning
confidence: 99%
See 3 more Smart Citations